THE EFFECT OF ACTIVATING THE FOUNDATIONS OF SCENARIO THINKING IN INCREASING THE PERFORMANCE OF BUSINESS ORGANIZATIONS - Башир Гессаби; Муса Гессаби (Экономика, профессия, бизнес)
In our time, the world is witnessing rapid and highly developed changes in the business environment of organizations, and we require them to constantly work on a path in accordance with the development required by this need for conditions, as the performance of organizations has become one of the most important basic pillars for the survival and continuation of organizations in a work environment characterized by developments and changes. There are not many organizations that are interested in analyzing the internal work system. economic and political variables directly and indirectly affect the strategic alternatives of organizations, which prompted many of them to develop alternative strategic options to confront these changes, by creating a set of possible scenarios in order to adapt in the face of obstacles and likely developments in the work environment in a more flexible and efficient manner.